Case Report: Decompressive Craniectomy for COVID-19 Malignant Cerebral Artery Infarction. Is Surgery a Good Option? - Sáez-Alegre, Miguel; García-Feijoo, Pablo; Millán, Pablo; Vivancos Sánchez, Catalina; Rodríguez Domínguez, Víctor; García Nerín, Jorge; Isla Guerrero, Alberto; Gandía-González, María Luisa (Frontiers in Neurology, 2021)
Introduction: SARS-CoV2 infection can cause a prothrombotic state which can lead to large cerebral vessel occlusion that can evolve to a malignant cerebral stroke. Decompressive craniectomy is a standard life-saving procedure indicated in patients who suffer a malignant cerebral stroke, however there is limited evidence about this procedure in the treatment of COVID-19-related malignant cerebral infarction. In the coming months, due to the rise in SARS-Cov2 infection, we are expected to face the challenge of treating more patients with COVID19 associated malignant cerebral stroke. These patients’ features are completely different from the patients that we have been treating for years, depicting a unique scenario without any evidence about the eligibility criteria for decompressive craniectomy. To our knowledge 7 cases of decompressive craniectomy due to malignant cerebral infarctions have been described, only 1 of them in the left middle cerebral artery. Methods: We report a 39-year-old female with no major risk factors for cerebrovascular disease, apart from oral contraception, and mild COVID-19 symptoms that suffered a left hemispheric syndrome, who underwent endovascular treatment with stenting and afterwards decompressive craniectomy due to worsening neurological status with unilateral unreactive mydriasis. We present the first case with those characteristics and make a comprehensive review of the available literature related to the surgical treatment for malignant strokes associated to COVID-19. Results: Eight patients including our case who underwent decompressive craniectomy for malignant cerebral stroke have been described to date. Mortality rate was 25%. Left middle cerebral artery (MCA) malignant stroke was found in two of the four MCA infarctions reported, both survived after decompressive craniectomy. Conclusions: Our results suggest that decompressive craniectomy should be considered as an effective live-saving treatment for COVID-19-related malignant cerebral strokes. Further studies with more patients will be necessary to achieve statistically significant results.